Elastic deuteron-triton scattering AT 37MeV - Belyuskina, O.O.; Grantsev, V.I.; Davydovskyy, V.V.; Kisurin, K.K.; Omelchuk, S.E.; Palkin, G.P.; Roznyuk, Yu.S.; Rudenko, B.A.; Saltykov, L.S.; Semenov, V.S.; Slusarenko, L.I.; Struzhko, B.G.; et al. (Вопросы атомной науки и техники, 2009)
Results of measurement of differential cross section of elastic scattering of deuterons by tritons at the laboratory energy of 37 MeV for the center-of-mass angles θc.m. ranging from 25° to 150° are presented. The experiment is carried out on the U-240 isochronous cyclotron of the Institute for Nuclear Research, National Academy of Science of Ukraine. Obtained experimental data is analyzed theoretically in the framework of microscopic nuclear diffraction model. Angular distributions of deuterons in a region of the main maximum (θc.m. ≤ 60° ) are described quite well at deuteron energies of 14.4, 37.0 and 39.9 MeV . An explanation of a broad secondary maximum emerging at low deuteron energies is proposed using the phenomenological quasiclassical approximation. The quasiclassical approximation allows to describe the angular distributions only qualitatively at large angles 60° < θc.m. < 150°, where the cross sections are quite small.